Zur Morphologie der Substantive in altniederländischen Ortsnamen. - Quak, Arend (Amsterdamer Beiträge zur Älteren Germanistik, 2019)
Old Dutch place names from the period 700–1100 are here used for the reconstruction of the morphology of Old Dutch nouns. The genitive singular and plural of the strong masculine and neuter are here scrutinized, as well as the dative plural of all nouns. In the course of the paper the meaning of some place names is revised as well.